Brain Metastases Status and Immunotherapy Efficacy in Advanced Lung Cancer: A Systematic Review and Meta-Analysis - Hu, Hao; Xu, Zhi-Yong; Zhu, Qian; Liu, Xi; Jiang, Si-Cong; Zheng, Ji-Hua (Frontiers in Immunology, 2021)
Background Brain metastases (BMs) indicate poor outcomes and are commonly excluded in immunotherapy clinical trials in advanced lung cancer; moreover, the effect of BM status on immunotherapy efficacy is inconsistent and inconclusive. Therefore, we conducted a meta-analysis to assess the influence of BM status on immunotherapy efficacy in advanced lung cancer. Methods Electronic databases and all major conference proceedings were searched without language restrictions according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. We extracted randomized clinical trials on lung cancer immunotherapy that had available overall survival (OS) and/or progression-free survival (PFS) data based on the BM status. All analyses were performed using random effects models. Results Fourteen randomized clinical trials with 9,089 patients were identified. Immunotherapy conferred a survival advantage to BM patients [OS-hazard ratio (HR), 0.72; 95% confidence interval (CI), 0.58–0.90; P = 0.004; and PFS-HR, 0.68; 95% CI, 0.52–0.87, P = 0.003]. Non-BM patients could also derive a survival benefit from immunotherapy (OS-HR, 0.76; 95% CI, 0.71–0.80; P <0.001; and PFS-HR, 0.68; 95% CI, 0.56–0.82, P <0.001). The pooled ratios of OS-HRs and PFS-HRs reported in BM patients versus non-BM patients were 0.96 (95% CI, 0.78–1.18; P = 0.72) and 0.97 (95% CI, 0.79–1.20; P = 0.78), respectively, indicating no statistically significant difference between them. Subsequent sensitivity analyses did not alter the results. Subgroup analyses according to tumor type, line of therapy, immunotherapy type, study design, and representation of BM patients reconfirmed these findings. Conclusion We demonstrated that BM status did not significantly influence the immunotherapy efficacy in lung cancer, suggesting that both BM and non-BM patients could obtain comparable benefits. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier (CRD42020207446).